Toward Computational Design of Catalysts for CO2 Selective Reduction via Reaction Phase Diagram Analysis. Issue 3 (30th January 2019) - Han, Mengru; Fu, Xiaoyan; Cao, Ang; Guo, Chenxi; Chu, Wei; Xiao, Jianping
Abstract: Chemical conversion of carbon dioxide (CO2 ) into value‐added chemicals, for example, ethanol, has been recognized to be one of the most effective ways of carbon sources cycling. However, the selectivity controlling of CO2 reduction is still a challenging problem due to the formation of a variety of products, such as methanol, methane, formic acid, and carbon monoxide, associating with complicated reaction mechanisms. Herein, a simple and effective theoretical analysis of "reaction phases diagram" to understand the selectivity of CO2 reduction, based on the principle of reaction free energies with sequential priority is proposed. Using this principle, the fundamental understanding of the formation of different products in CO2 reduction is rationalized. On the basis of reaction free energies' analysis, the selectivity trends of CO2 reduction to methane, methanol, and ethanol from a number of experiments are discussed. At the end, the selectivity trends with a computer algorithm of searching full reaction pathways, explaining well the effects from catalyst sizes, substrate observed in experiments, are confirmed. Abstract : Carbon dioxide (CO2 ) reduction for producing ethanol and other products is critical but challenging. Herein, a "reaction phases diagram" to understand the selectivity of CO2 reduction is proposed. As elemental metals are not always in the scope of high selectivity for ethanol production, some efficient strategies including size, alloy, and steric effects are further addressed to tune the product selectivity of catalysts.